নারী, মানবধিকার ও রাজনীতি - কামাল, সুলতানা (ঢাকা : ইত্যাদি গ্রন্থ প্রকাশ, 2010)
Articles on women's rights and political activity with reference to Bangladesh.
In Bengali.
Keywords: Women's rights -- Bangladesh; Women -- Political activity -- Bangladesh; Bangladesh -- Politics and government -- 1971-